Treatment of apathy in stroke patients: a systematic review - Ruiz-Franco, Maria Luisa; Amaya-Pascasio, Laura; Gil-Rodríguez, Mercedes; Arjona-Padillo, Antonio; García-Pinteño, José; Rodriguez-Sanchez, Antonio Jose; Sánchez-Kuhn, Ana; Flores, Pilar; Martinez-Sanchez, Patricia (Frontiers in Neurology, 2025)
IntroductionPost-stroke apathy is a prevalent yet frequently underdiagnosed neuropsychiatric syndrome, reported in up to one-third of stroke survivors, and is consistently associated with poorer functional recovery and cognitive decline. We aimed to review the current evidence on available pharmacological and non-pharmacological treatments for post-stroke apathy, and to evaluate their efficacy and safety.MethodsA systematic review was conducted following PRISMA guidelines and registered in the PROSPERO database (CRD42022332559). We searched PubMed, Web of Science, and Scopus for randomized and non-randomized clinical trials published until November 2024. Eligible studies included adults with ischemic or hemorrhagic stroke and a defined diagnosis of apathy. Interventions included pharmacological treatments and non-pharmacological strategies, such as neuromodulation techniques. Data extraction and risk of bias assessment were independently performed by two reviewers using the RoB-2 tool.ResultsTen clinical trials involving 2,359 patients were included. Pharmacological interventions with escitalopram and donepezil (alone or combined with intensive language action therapy) showed potential benefits. Nefiracetam yielded mixed results depending on dose and coexisting depression. Non-pharmacological approaches such as problem-solving therapy, motor relearning programs, strategy training, and complex rehabilitation programs demonstrated significant improvement in apathy scores. High-frequency repetitive transcranial magnetic stimulation also showed efficacy. However, heterogeneity in study design and apathy assessment scales limited direct comparisons.ConclusionSeveral interventions, including escitalopram, donepezil, motor relearning programs, strategy training, and rTMS, have demonstrated potential effectiveness in treating post-stroke apathy. Nevertheless, evidence remains scarce and heterogeneous, underscoring the need for larger, high-quality randomized controlled trials to establish definitive treatment guidelines.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42022332559.